PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA OUTLET NASI KEBULI YAMAN KUTA BUMI TANGERANG - Nining Puspyta Sari; Mada Faisal Akbar (Journal of Research and Publication Innovation, 2025)
The aim of this research is to find out and test how influential product quality and promotion are on purchasing decisions for Nasi Kebuli Yamana Kuta Bumi at the Tangerang branch. .This research method is quantitative with an associative approach. The sampling technique used was purposive random sampling which used a sample of 100 respondents. Data collection techniques use questionnaires and literature study. The data analysis techniques used are instrument testing, classical assumption testing, linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of partial hypothesis testing between product quality and promotion obtained a value of tcount 8.813 > ttable 1.660 with a significance level of 0.000 < 0.05. So H0 is rejected and Ha is accepted. The results of partial hypothesis testing between service quality and product quality obtained a value of tcount 1.998 > ttable 1.660 with a significance level of 0.049 < 0.05. So H0 is rejected and Ha is accepted. The results of simultaneous hypothesis testing between product quality and promotion decisions obtained an Fcount value of 178.090 > Ftable 3.09 with a significance level of 0.000 < 0.05. So H0 is rejected and Ha is accepted. The results of the coefficient of determination of promotion and service quality simultaneously contributed 78.6% while the remaining 21.4% was caused by other variables.